Comparing Several Variances with a Control in Direction-mixed Families of Hypotheses. Issue 7 (8th August 2016) - Chauhan, Rajvir Singh; Singh, Parminder; Kumar, Narinder
Abstract : This article deals with simultaneous comparisons of k(k ⩾ 1) populations with a control population with respect to variance in direction-mixed families of hypotheses. Computation of critical constants required for the implementation of the proposed procedures is discussed and selected values of the critical constants are tabulated. Power comparison of the proposed procedures with their existing competitors is carried out using Monte Carlo simulation. An example is given to illustrate the implementation of proposed procedures.